2012
DOI: 10.1016/j.drugalcdep.2011.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal inhibitory effects of intravenous d-methamphetamine self-administration and wheel activity in rats

Abstract: Background Some epidemiological and cessation studies suggest physical exercise attenuates or prevents recreational drug use in humans. Preclinical studies indicate wheel activity reduces cocaine self-administration in rats; this may, however, require the establishment of compulsive wheel activity. Methods Effects of concurrent wheel activity on intravenous d-methamphetamine (METH) self-administration were examined in male Wistar and Sprague Dawley rats with negligible prior wheel experience. Wistar rats sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
70
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 46 publications
12
70
0
Order By: Relevance
“…In that study, the relationship between exercise and cocaine self-administration was reciprocal, in that concurrent access to cocaine also decreased wheel running, and this effect was observed in both males and females. Consistent with those findings, Miller et al (2011) reported that concurrent access to a running wheel decreased responding maintained by methamphetamine, provided that the wheel was concurrently available at the outset of self-administration training. Using a slightly different experimental design, Smith et al (2008) reported that aerobic exercise reduced cocaine self-administration even when a running wheel was not concurrently available during the test sessions.…”
Section: The Effects Of Exercise On Drug Self-administration: Cocainementioning
confidence: 65%
See 1 more Smart Citation
“…In that study, the relationship between exercise and cocaine self-administration was reciprocal, in that concurrent access to cocaine also decreased wheel running, and this effect was observed in both males and females. Consistent with those findings, Miller et al (2011) reported that concurrent access to a running wheel decreased responding maintained by methamphetamine, provided that the wheel was concurrently available at the outset of self-administration training. Using a slightly different experimental design, Smith et al (2008) reported that aerobic exercise reduced cocaine self-administration even when a running wheel was not concurrently available during the test sessions.…”
Section: The Effects Of Exercise On Drug Self-administration: Cocainementioning
confidence: 65%
“…It is important to note that in studies in which exercise was used as an alternative reinforcer, the decrease in drug self-administration could not be attributed to simply having less time available to self-administer the drug. In all existing studies, test sessions lasted several hours or longer (e.g., Kanarek et al, 1995; Cosgrove et al, 2002; Zlebnik et al, 2010; Miller et al, 2011), and the cumulative amount of time spent on both activities was less than the total duration of the session. Consequently, the ability of exercise to decrease drug self-administration is generally attributed to a decrease in the relative reinforcing strength of the drug when both are concurrently available.…”
Section: Mechanisms Of Exercise On Drug Self-administration: Behaviormentioning
confidence: 99%
“…The beneficial effect of physical activity is most notable when access to a running wheel occurs during the self-administration session (Cosgrove et al, 2002;Kanarek et al, 1995;Zlebnik et al, 2012). However, when access to a running wheel is implemented either before or after daily operant conditioning sessions, a decrease in intravenous self-administration also is obtained across different various drugs, including cocaine (Smith et al, 2008b;, methamphetamine (Engelmann et al, 2013;Miller et al, 2012), heroin (Smith and Pitts, 2012) and morphine (Hosseini et al, 2009). Physical activity also decreases the escalation of self-administration (Engelmann et al, 2013;Zlebnik et al, 2012) and reinstatement (Lynch et al, 2010;Sanchez et al, 2013;Thanos et al, 2013;Zlebnik et al, 2010).…”
Section: Preclinical Evidencementioning
confidence: 91%
“…Preclinical studies have supported these findings by reporting that exercise, which is typically operationalized as running on a treadmill or in an activity wheel, decreases the self-administration of many drugs of abuse. In laboratory rats, for instance, exercise reliably decreases the positive reinforcing effects of psychomotor stimulants, including cocaine and methamphetamine (Cosgrove et al 2002; Miller et al 2012; Smith and Witte 2012; Smith et al 2008; 2011), and the positive reinforcing effects of opioids, including heroin and morphine (Hosseini et al 2009; Smith and Pitts 2012). Moreover, these effects are typically observed across doses, subject populations, and schedules of reinforcement (for review, see Lynch et al 2013; Smith and Lynch 2012).…”
Section: Introductionmentioning
confidence: 99%